Internal and External Factors Influencing Nurses' Compliance in Risk of Fall Prevention Procedures - Gunawan, Arif Candra; Wijaya, Dodi; Ardiana, Anisah (Babali Nursing Research, 2025)
Introduction: Nursing care is the most essential element in health services. Professional nurses must provide safe, effective services and participate in maintaining patient safety. Safety for patients is essential because it can increase the value of professionalism. The research aims to analyze internal and external factors regarding nurses' compliance in implementing Standard Operating Procedures to prevent the risk of falls.Methods: This research used an analytical observational design with a cross-sectional approach using a sample of 107 respondents from two hospitals in Jember.Results: The results showed that internal factors influenced nurse compliance in implementing SOP for patients at risk of falling (p-value 0.045). Regarding external factors, it was found that compliance in implementing SOP for patients with fall risk did not have a significant effect (p-value 0.948).Conclusion: Continuous training, effective supervision, and work environment support are important to increase nurses' compliance in implementing SOPs to prevent falls. This research recommends strengthening hospital training and supervision strategies to increase nurse compliance, ultimately improving overall patient safety.